2007
DOI: 10.2341/06-83
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Marginal Ridge Thickness on the Fracture Resistance of Endodontically-treated, Composite Restored Maxillary Premolars

Abstract: This study evaluated the effect of varying thicknesses of marginal ridge on the fracture resistance of endodontically-treated maxillary premolars restored with composite.Ninety non-carious maxillary premolars, extracted for orthodontic reasons, were selected for this experimental in vitro study. The teeth were randomly assigned to six groups (n=15). Group 1 received no preparation. In groups 2 through 6, the premolars were root filled and DO preparations were created, while MOD preparations were also created f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 17 publications
3
25
1
3
Order By: Relevance
“…Group 2 recovered 58% of the resistance of a sound tooth, group 3 35%, and group 4 41%. These findings are in agreement with those of other studies 36,37,40 that verified that the different restorative techniques did not restore the resistance of a sound tooth. Nevertheless, the use of adhesive restorations has been recommended for reinforcing remaining dental structures, 38,41 even if full strength is not recovered.…”
Section: Discussionsupporting
confidence: 83%
“…Group 2 recovered 58% of the resistance of a sound tooth, group 3 35%, and group 4 41%. These findings are in agreement with those of other studies 36,37,40 that verified that the different restorative techniques did not restore the resistance of a sound tooth. Nevertheless, the use of adhesive restorations has been recommended for reinforcing remaining dental structures, 38,41 even if full strength is not recovered.…”
Section: Discussionsupporting
confidence: 83%
“…Scotti et al () found the remaining wall thickness to be a very important clinical parameter in the resistance of fracture in endodontically treated premolars and suggested that an axial wall thickness of less than 2 mm is an indication for cuspal coverage to improve the fracture resistance in maxillary premolars. Other in vitro studies have reported a reduction in tooth resistance to fracture with a wider isthmus preparation in MO/DO and MOD cavities (Mondelli et al, ; Reagan et al, ) and with a marginal ridge thicknesses of less than 1 mm in ETT (Shahrbaf, Mirzakouchaki, Oskoui, & Kahnamoui, ).…”
Section: Discussionmentioning
confidence: 92%
“…Commonly, the tooth has been structurally compromised by removal of tooth substance during endodontic treatment and restorative procedures. Moreover, endodontically treated teeth can be easily fractured because of pulp chamber roof removal, 8 mainly when the marginal ridge is thin or totally removed 22 . During mastication, occlusal contacts occur on almost every chewing cycle.…”
Section: Discussionmentioning
confidence: 99%